Antihelminthic and anticoccidial effects of vernonia amygdalina in goats (2014)
The deteriorating and adverse effect of chemoprophylaxis and chemotherapy in livestock production has been well documented, however, not many alternatives with minimal or no side effects are available for treatment and control of parasite infections. Vernonia amygdalina, also known as bitter leaf, has been reported to have various medicinal properties, however, its antihelminthic and anticoccidial properties in goats has not been investigated despite anecdotal reports of its antidiarrhoiec effects in the specie. 20 goats were bought from various households, stabilized, divided into treatment group of fifteen and control group of five. They were fed on pasture and allowed to acquire natural parasite infection that was confirmed by feacal count and culture. The treatment groups were fed with V amygdalina leaves and young stalk ad libitum for two days while the control group was denied access to the plant. Feacal samples were collected on days 1, 2, 4 and 7, post treatment and sent to laboratory for analysis. The ingestion of Vernonia amygdalina was effective in the clearance of helminth eggs and coccidian cysts with an efficacy of 100% for helminths and 99.4% for coccidia. Five goat owners with herds ranging between five to twelve in number diagnosed with helminth infecton were asked to feed V amygdalina leaves to the goats once a week. All the goats were free of helminth infection within the period of four weeks that they were monitored. The effect of Vernonia amygdalina on helminth and coccidian parasites in goats has corroborated findings by other authors in other animal species and man. The plant provides an alternative and natural antiparasitic agent for goat heminth and coccidian that is environment friendly and without the effect of chemical residues. Further, studies on the dose may have to be carried out